2005
DOI: 10.1097/01.ju.0000164725.53219.be
|View full text |Cite
|
Sign up to set email alerts
|

The Tunica Vaginalis Dorsal Graft Urethroplasty: Experimental Study in Rabbits

Abstract: In the current study we noted that a tunica vaginalis graft placed dorsally can be a successful urethral substitute in the animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 18 publications
4
18
0
3
Order By: Relevance
“…All animals demonstrated a patent and functional urethra, as evidenced by radiographic and histological analyses. There was no evidence of infection or fistula (5).…”
Section: Commentsmentioning
confidence: 92%
“…All animals demonstrated a patent and functional urethra, as evidenced by radiographic and histological analyses. There was no evidence of infection or fistula (5).…”
Section: Commentsmentioning
confidence: 92%
“…Tunica vaginalis can also be employed as an optional graft to reconstruct the urethral plate in the three-in-one concept and has already been investigated [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Other advantages such as a lack of hair follicles, a good tensile and physical property resulting in better sutures holding and a very good vascularization were reported. Over the years, it has been used in experimental studies for surgical techniques in urethroplasty (Calado et al 2005, Khoury et al 1989, Talja et al 1987 and in general, good results were observed. In 1998, a study compared an onlay flap with a tube flap performed on a New Zealand rabbit model with a control group.…”
Section: Tissue Engineering 490mentioning
confidence: 99%